(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Due to low temperatures, decreased immunity, and increased indoor activity, the winter months have been related to a major increase in viral respiratory diseases. The most common viral infections are influenza (flu), respiratory syncytial virus (RSV), and adenovirus, which frequently cause common clinical symptoms such as fever, cough, cold, and difficulty breathing. For effective treatment and the prevention of problems, early and clear division is necessary due to differences in appearance. Ayurveda, Unani, and homoeopathy are examples of traditional medical systems that promote a holistic and individualized treatment of disease by applying their own theoretical frameworks to describe these diseases. Influenza, RSV, and adenovirus as they are defined in these traditional systems are theoretically and scientifically described in this article. The methods covered are not meant to be used as evidence-based therapeutic treatment recommendations; rather, they are founded on traditional interpretations and classical ideas. The goal of the study is to highlight conventional viewpoints while recognizing the significance of conventional medical care in the treatment of viral diseases.